Time for Hegel: History and the Absolute Now - Reid, Jeffrey (Université d'Ottawa | University of Ottawa, 2022)
The book chapter examines Hegelian temporality, how the philosopher reconciles the Greek notion of time as an eternal "Now", as presented through Karl Löwith's interpretation of Aristotle, and the Christian world's notion of time as historically informed. The article approaches the question through a critique of Löwith's reading of Hegel in his monumental Between Hegel and Nietzsche. The chapter is a reworked, translated version of an earlier published French book chapter.
Keywords: Time; Löwith; Young Hegelians; Left Hegelians; History; eternity